A Short History of the Beginnings of Hospital Information Systems in Argentina - Yácubsohn, V. (Yearbook of Medical Informatics, 2012)
Objectives: To describe the development of early health information systems in Argentina and their impact on the development of professional societies in the disciplineMethods: The first hospital information systems and health surveillance systems in Argentina are described and related to the rise of professional organizations for health informatics.Results: The early health information systems in Argentina are related to precursor developments in medical informatics.Conclusions: Argentina saw a number of hospital information systems developed starting in 1977, which had an important influence on the practice and experience in medical informatics in the country, and the participation of Argentine professionals in national, regional, and international activities in the field
Keywords: Hospital information systems; Argentina; history; 1980s; professional associations; health informatics